Фонічний компонент у експресивній системі поетичного тексту - Мойсієнко, А.К. (Мовознавство, 2018)
Статтю присвячено проблемі експресивності поетичного тексту, організації
експресивних єдностей у художньому творі. На особливу увагу заслуговує фонічний
компонент, який, виступаючи структурним складником будь-якого текстового утворення, а надто — поетичного, стає неодмінним чинником динамізації та естетизації
художньої структури, у поєднанні з іншими чинниками — граматичними, образними тощо — відіграє надзвичайно виразну роль в організації мистецького твору як
цілісної експресивної єдності. The paper describes the problem of poetical texts expressiveness and arrangement
of expressive textual structures. By «expressiveness» we mean emotional and logical
emphasizing, high intensity of the textual expression that can be achieved both with the
help of a single element from the wide language tools variety or a gradation of quantitative
and qualitative features on the different language levels, and also by poetical means in
their endogenous and exogenous manifestation. The author explores the peculiarities of
the creation of expressive structures in the modern Ukrainian poetry and gives special
attention to the expressive unities with the dominant phonic component. The observation
of the phonic scheme of such unities proves that the intensity of a single word or first line
can be accumulated in a certain sound composition on a broader background in respect of
the semantic, compositional collision of the work. Also, a header plays an important role in
the creation of appropriate expressive unity because it always possesses the strong position
in a text and its intentionality, located at the semantic level, becomes a necessary factor of
support to this unity at the other language levels, especially phonic. The expressiveness
of sound image based on the numerous phonic repetitions in the corresponding syntactic
(chiasmic) structures, poetic (panthorhyme) can be explained by emphasizing on different
senses, psychologism of semantic bias that is achieved using certain phonic composition.
In general, phonic element, being a component of any textual construction, especially
poetical, becomes an essential factor of dynamization and aestethization of poetic text
and taken in combination with the other factors (grammatical, figurative etc.) plays an
important role in the composition of literary work as a holistic expressive unity.